2021
DOI: 10.1159/000513951
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Survival in Chronic Hemodialysis Patients: A 10-Year Longitudinal Follow-Up Analysis

Abstract: <b><i>Background:</i></b> Risk factors of mortality in chronic hemodialysis patients have not yet been sufficiently evaluated. In particular, chronological transits and interactions of the impact of risk factors have rarely been described. <b><i>Methods:</i></b> This study is a post hoc analysis of the participants in the Olme­sartan Clinical Trial in Okinawan Patients under OKIDS (OCTOPUS) study conducted between June 2006 and June 2011. We additionally followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…When we extended the observation period of the previous RCT study participants to 10 years [66] and investigated the combination of S-Alb and serum phosphate (S-Pi) on survival, we found that the best survival was seen in those patients with higher S-Alb and lower S-Pi, while the worst survival was seen in those patients with lower S-Alb and lower S-Pi. In chronic HD patients, S-Pi appears to be a surrogate of protein intake [67].…”
Section: Dialysis Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…When we extended the observation period of the previous RCT study participants to 10 years [66] and investigated the combination of S-Alb and serum phosphate (S-Pi) on survival, we found that the best survival was seen in those patients with higher S-Alb and lower S-Pi, while the worst survival was seen in those patients with lower S-Alb and lower S-Pi. In chronic HD patients, S-Pi appears to be a surrogate of protein intake [67].…”
Section: Dialysis Patientsmentioning
confidence: 99%
“…In a recent study of 461 chronic HD patients with a median follow-up of 10 years, 46% of patients died [67]. The main causes of death were infection (34%) and cardiovascular disease (31%).…”
Section: Weight Change As a Predictor Of Mortalitymentioning
confidence: 99%
“…1 Although the discrepancy was observed in relatively non-obese HD participants of our study, the means of baseline BMI at the enrolment were 23.0±3.7 in deceased patients and 22.7±3.4 in survived patients, respectively. 8 Further, comprehensive baseline data and a high follow-up rate (98.3%) allowed us to observe less biased associations.…”
Section: A C C E P T E D V E R S I O Nmentioning
confidence: 96%
“…In the study cohort, 5% of patients died every year. 8 Therefore, a 3-year follow-up period would have reduced the sample size by 15% or increased the amount of missing data, both of which would affect the study's statistical power and introduce a selection bias. Additionally, a 1-year timeframe cannot distinguish between long-term BW change and acute BW change caused by haemodynamic change or infectious diseases; thus, our analysis excluded BW changes within 1 year.…”
Section: Measurements Of Bw Body Mass Index and Covariatesmentioning
confidence: 99%
See 1 more Smart Citation